2013
DOI: 10.1063/1.4800780
|View full text |Cite
|
Sign up to set email alerts
|

Laser-enhanced cavitation during high intensity focused ultrasound: An in vivo study

Abstract: Laser-enhanced cavitation during high intensity focused ultrasound (HIFU) was studied in vivo using a small animal model. Laser light was employed to illuminate the sample concurrently with HIFU radiation. The resulting cavitation was detected with a passive cavitation detector. The in vivo measurements were made under different combinations of HIFU treatment depths, laser wavelengths, and HIFU durations. The results demonstrated that concurrent light illumination during HIFU has the potential to enhance cavit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
(35 reference statements)
1
13
0
Order By: Relevance
“…Hu et al demonstrated that combined laser and ultrasound can be used to selectively target micro‐vessels without damaging the surrounding . Similar studies have described how combined laser and ultrasound resulted in increased cavitation , which has been used with optically absorbent nanoparticles for targeted cavitation . These previous ablation studies have looked at internal applications, while this study intends to explore dermatological applications.…”
Section: Introductionmentioning
confidence: 79%
“…Hu et al demonstrated that combined laser and ultrasound can be used to selectively target micro‐vessels without damaging the surrounding . Similar studies have described how combined laser and ultrasound resulted in increased cavitation , which has been used with optically absorbent nanoparticles for targeted cavitation . These previous ablation studies have looked at internal applications, while this study intends to explore dermatological applications.…”
Section: Introductionmentioning
confidence: 79%
“…a blood vessel), the laser-induced photoacoustic wave can converge into the center and achieve a significantly high acoustic pressure and produce cavitation44, which is referred to as “cold bubbles” and has been observed in cells45. Unlike other use of therapeutic ultrasound and laser irradiation4647484950, when ultrasound and laser irradiation are concurrently applied, a portion of the ultrasound waves can modulate the transient thermal-elastic negative stress produced through photospallation, which will increase the cavitation efficiency because of the greater negative pressure31. One of the key features of photoacoustic cavitation is that cavitation may be induced at a laser energy level that is much lower than that needed for laser thermal therapies (such as photothermolysis and photocoagulation) because photoacoustic cavitation is not a strictly thermal effect.…”
Section: Discussionmentioning
confidence: 99%
“…When a laser pulse is absorbed by hemoglobin, the tissue is excited and the photoacoustic effect occurs. The concurrent application of ultrasound significantly increases the likelihood of micro-cavitation in the blood vessel31. The produced cavitation can then be further enhanced and driven by the subsequent ultrasound pulses.…”
mentioning
confidence: 99%
“…Hydrophobic particulates (Soltani 2013), perfluorocarbon droplets (Pajek et al 2014) and focused laser pulses (Cui et al 2013) have been used to nucleate cavitation effectively during sonothrombolysis. However, ultrasound contrast agents (UCAs), or stabilized microbubbles, are also used to nucleate cavitation.…”
Section: 2 Mechanisms Of Thrombolytic Enhancementmentioning
confidence: 99%